2010
DOI: 10.1103/physrevb.81.195114
|View full text |Cite
|
Sign up to set email alerts
|

Crystal-field and Kondo-scale investigations ofCeMIn5(M=Co, Ir, and Rh): A combined x-ray absorption and inelastic neutr

Abstract: Linear-polarized soft-x-ray absorption ͑XAS͒ and inelastic neutron scattering ͑INS͒ experiments have been performed on CeMIn 5 with M = Rh, Ir, and Co to determine the crystal-field scheme and characteristic Kondo temperatures T ‫ء‬ for the hybridization between 4f and conduction electrons. The ground-state wave functions are determined from the polarization-dependent soft-XAS data at the cerium M 4,5 edge and the crystal-field splittings from INS. The characteristic temperature T ‫ء‬ has been determined from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
72
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 40 publications
(62 reference statements)
11
72
1
Order By: Relevance
“…It has been shown that the analysis of the LD effects using the ligand field multiplet (LFM) model gives a good quantitative description of the CEF ground state 26,[28][29][30] . In CeAgSb 2 , the CEF splitting energies from the ground state to the first and second excited states (∆ 1 and ∆ 2 ) have been determined to be 5.2 meV (≈60 K) and 12.5 meV (≈145 K) from the INS measurements, in which the CEF ground state is |±1/2 and the first and second exited levels are dominated by |±3/2 and |±5/2 , respectively 8 .…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the analysis of the LD effects using the ligand field multiplet (LFM) model gives a good quantitative description of the CEF ground state 26,[28][29][30] . In CeAgSb 2 , the CEF splitting energies from the ground state to the first and second excited states (∆ 1 and ∆ 2 ) have been determined to be 5.2 meV (≈60 K) and 12.5 meV (≈145 K) from the INS measurements, in which the CEF ground state is |±1/2 and the first and second exited levels are dominated by |±3/2 and |±5/2 , respectively 8 .…”
Section: Resultsmentioning
confidence: 99%
“…It would also be interesting to explore the effects of uniaxial strain on the magnitude of elastic softening, T v , and T c . Making the crystal structure more or less tetragonal with uniaxial strain along theĉ axis should tune the 5f degeneracy (34,35) and thus, the valence fluctuations: uniaxial strain may be the tuning parameter required to reach the valence quantum critical point and may realize even higher T c values than hydrostatic pressure.…”
Section: Physicsmentioning
confidence: 99%
“…Its magnetic variants, x-ray magnetic linear and circular dichroism (XMLD, XMCD) constitute sensitive element and orbital specific probes of magnetic polarization and anisotropy [15][16][17][18][19][20]. XMCD was successfully utilized to reveal the presence of magnetic Kondo screening in CePt 5 /Pt(111) [21].In the present letter we demonstrate that the combined use of linear and magnetic circular dichroism allows us to determine the crystal field structure without recourse to e. g. inelastic neutron scattering, as in some previous work [7][8][9]. Our chosen example of an ultrathin Ce-Ag surface intermetallic furthermore highlights a threefold advantage of this approach.…”
mentioning
confidence: 62%
“…In the present letter we demonstrate that the combined use of linear and magnetic circular dichroism allows us to determine the crystal field structure without recourse to e. g. inelastic neutron scattering, as in some previous work [7][8][9] the same installation and therefore can be performed in situ within a single experimental run. Second, the splittings turn out to be of the order of 1 meV only, making their discrimination from quasi-elastic scattering a difficult task.…”
mentioning
confidence: 77%
See 1 more Smart Citation